Inhibiting Pathogen Surface Adherence by Multilayer Polyelectrolyte Films Functionalized with Glucofuranose Derivatives - Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Molina, C; Silva-Molina, C (American Chemical Society, 2018)
Inhibiting pathogenic bacterial adherence on surfaces is an ongoing challenge to prevent the development of biofilms. Multilayer polyelectrolyte films are feasible antibacterial materials. Here, we have designed new films made of carbohydrate polyelectrolytes to obtain antibacterial coatings that prevent biofilm formation. The polyelectrolyte films were constructed from poly(maleic anhydride-alt-styrene) functionalized with glucofuranose derivatives and quaternized poly(4-vinylpyridine) N-alkyl. These films prevent Pseudomonas aeruginosa and Salmonella Typhimurium, two important bacterial contaminants in clinical environments, from adhering to surfaces. When the film was composed of more than 10 layers, the bacterial population was greatly reduced, while the bacteria remaining on the film were morphologically damaged, as atomic force microscopy revealed. The antibacterial capacity of the polyelectrolyte films was determined by the combination of thickness, wettability, surface energy, and most importantly, the conformation that polyelectrolytes adopt the function of nature of the carbohydrate group. This polyelectrolyte film constitutes the first green approach to preventing pathogenic bacterial surface adherence and proliferation without killing the bacterial pathogen. © 2018 American Chemical Society.